PELATIHAN PEMBUATAN DODOL ALPUKAT DI DESA LENEK DUREN - M. Afyadi Perwira; Nisak, Sri Hidayatun; Febrianti, Amaliah; Julita, Delisa; Akbar, Zulfikar Ibnu Ali; Mujahid, Imam; Fitrianiningsih, Fitrianiningsih; Safitri, Novita; Erlina, Erlina; Hamid, Ahyar; Merta , I Wayan (Jurnal Wicara, 2025)
Lenek Duren Village, located in East Lombok Regency, West Nusa Tenggara Province, has rich natural potential, especially in avocado production. Although alpuka is known for its antioxidant content and distinctive taste, the utilization of this fruit is still limited as fresh consumption. To address this issue, a training on avocado dodol making was conducted on January 23, 2025, aiming to improve the community's understanding of avocado processing. The training involved three stages: selection of ripe avocados, trial dodol making, and hands-on training. The results of the training showed that avocado dodol has a unique flavor that combines sweetness and bitterness, and was enthusiastically received by the community.